Le fratture diafisarie del femore - Mazzi, M.; Micaglio, A.; Schiavon, R. (Lo Scalpello - Journal, 2018)
FEMORAL SHAFT FRACTURE IN CHILDRENPaediatric femoral shaft fractures account for less than 2% of all fractures in children. Modalities of treatment varymostly according to age, with fracture pattern and site having a lesser impact. There appears to be some consensus inthat the method we choose must lead to shortening the hospital stay, be comfortable for the patient, provide suitablestability to the fracture and have less complications. Trends in treatment have varied over time. Significantcomplications are relatively rare. Because of the limited rotational remodelling it is important to avoid malrotation.